A kind of anticorrosive slurry of modified graphene chloroprene rubber and preparation method thereof
By modifying the anticorrosion slurry of graphene chloroprene, combined with nano-grade particles and maleic anhydride surface modifier, the problems of poor initial bonding performance and insufficient storage stability of chloroprene latex adhesive are solved, and efficient bonding and extended service life are achieved.
Patent Information
- Application Number
- CN202411280270.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-04
AI Technical Summary
During use, existing neoprene latex adhesives have problems such as poor initial bonding performance, slow drying speed, easy freezing and poor storage stability.
The anticorrosion slurry of modified graphene chloroprene is used to prepare nano-grade acrylate emulsion particles and chloroprene latex particles, and a modified aqueous chloroprene latex system is constructed under the action of hydrocarbon solvents. Combined with a combination of maleic anhydride surface modifier and graphene oxide, a modified slurry with high tensile strength, heat resistance and fatigue resistance are formed, and a preservative is added therein to extend the bonding time.
It significantly improves the initial adhesion and drying speed of the adhesive, enhances the bonding effect, and effectively extends the storage stability and service life of the product.
Smart Images

Figure CN119752354A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-corrosion mortar and a preparation method thereof, and in particular to an anti-corrosion mortar of modified graphene chloroprene rubber and a preparation method thereof. Background Art
[0002] Neoprene is the first synthetic rubber compound to be mass-produced. As an adhesive, neoprene has a wide range of applications and has the characteristics of high initial adhesion and high bonding strength. It is mainly used in the decoration of homes and public facilities, the wood industry, the shoe industry and other industries. In the production of solvent-based adhesives, neoprene has been widely used in many fields because of its good comprehensive properties.
[0003] For chloroprene latex with a high gel content, it has relatively good high-temperature bonding performance, but also exhibits poor initial bonding performance. The reason may be that the molecular movement of the polymer is restricted by the gel structure, which hinders the internal entanglement of the polymer molecules. For solvent-based adhesives, the formation of its gel has little to do with the size of the polymer molecular weight. When the molecular weight is high, only a linear or branched structure will be formed inside it. From this phenomenon, it can be seen that the increase in molecular weight will cause a tighter entanglement inside the molecule, and the strength of its initial bonding will also increase. According to the above inferences, when using emulsion polymerization to prepare water-based chloroprene latex, the type of emulsifier used is generally anionic or non-ionic surfactants, and polyvinyl alcohol (PVA) is widely used in the preparation of water-based latex. In a new type of chloroprene latex ALX-600, although it is composed of sol, it has less gel components. This type of chloroprene latex has good high-temperature bonding strength, and its initial bonding performance has also been improved to a certain extent; and after a certain period of time, the glue often corrodes, reducing the bonding effect; in the current application field, water-based chloroprene latex has been widely used as a water-based adhesive, and the chloroprene latex water-based adhesive prepared by a certain method using chloroprene latex has become the direction of further development of chloroprene latex adhesives. However, water-based adhesives also have certain defects, such as slow drying speed, poor initial adhesion, easy freezing, and poor storage stability. In order to improve these defects of water-based adhesives and improve the comprehensive performance of chloroprene latex water-based adhesives in practical applications, corresponding modification work is often required for better application. Summary of the invention
[0004] Technical issues solved
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides an anti-corrosion slurry of modified graphene chloroprene rubber and a preparation method thereof, which can effectively solve the problems generated during the use of chloroprene rubber in the prior art.
[0006] Technical Solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] The invention provides an anticorrosive mortar of modified graphene chloroprene rubber, which is characterized in that the formula ratio is as follows by weight: 100-120 parts of chloroprene rubber mortar, 50-73 parts of dioctyl ester, 2-5 parts of graphene oxide, 20-30 parts of acrylic ester emulsion, 16-20 parts of maleic anhydride grafted graphene solution, 5-10 parts of hydrocarbon solvent, 40-80 parts of water, 3-5 parts of sepiolite and 5-15 parts of preservative.
[0009] Furthermore, the chloroprene rubber slurry includes chloroprene rubber particles, and the particle size distribution range of the chloroprene rubber particles is 60-100 nm. The acrylate emulsion includes acrylate particles, and the particle size distribution range of the acrylate particles is 5-20 nm.
[0010] Furthermore, the hydrocarbon solvent is coated on the surface of the acrylic ester particles and the chloroprene rubber particles, and the hydrocarbon solvent is selected from any one of n-hexane, cyclohexane and isohexane.
[0011] Furthermore, the preparation of maleic anhydride grafted graphene solution includes the following steps: S1: preparing graphene oxide by oxidizing natural graphite through Hummers method or improved Hummers method; S2: dispersing the graphene oxide obtained in step S1 and maleic anhydride in an organic solvent (such as dimethylformamide, DMF) to prepare a suspension; S3: grafting maleic anhydride onto the graphene oxide; S4: using the maleic anhydride grafted graphene oxide obtained in step S2 as a raw material, adding a free radical initiator, and reacting with styrene and maleic anhydride at 80-95° C. for 1-3 hours; S5: washing the reaction product with a solvent, centrifuging and drying it, to obtain a modified maleic anhydride copolymer grafted graphene.
[0012] Furthermore, in the process of preparing the maleic anhydride grafted graphene solution, when S2 prepares the suspension, the reaction needs to be maintained at 45-90°C for 2-4 hours, and the mass ratio of graphene oxide to maleic anhydride grafted graphene solution is 2:9-3:30.
[0013] Furthermore, the sepiolite is a powdered solid.
[0014] Furthermore, the free radical initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile or benzoyl peroxide.
[0015] A method for preparing a modified graphene chloroprene anticorrosive mortar comprises a modified graphene chloroprene anticorrosive mortar, wherein the preparation of the modified graphene chloroprene anticorrosive mortar comprises the following steps: S1: taking 20-30 parts of acrylic emulsion, 100-120 parts of chloroprene mortar, 5-10 parts of hydrocarbon solvent, 40-80 parts of water, and 3-5 parts of sepiolite in order by weight; S2: mixing and dispersing the sepiolite and water, and then adding acrylic acid; Ester emulsion and chloroprene rubber slurry, continue to stir and disperse, then add hydrocarbon solvents, pressurize and stir to mix and then discharge; S3: add graphene oxide to dioctyl ester with a weight of 50-60 times, heat to 50-60°C, and stir at high frequency for 2-8 hours to obtain product A; S4: add maleic anhydride; S5: after sepiolite and water are mixed and dispersed, add product A in S3, then add hydrocarbon solvents and preservatives, pressurize and stir to mix and then discharge.
[0016] Furthermore: the graphene oxide is 5-10% of the mass of the chloroprene latex.
[0017] Finally: the molar ratio of graphene oxide to maleic anhydride is 1:1.7-2, the temperature needs to be raised to 70-80°C, and the stirring is continued evenly for 4-6 hours.
[0018] Beneficial Effects
[0019] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:
[0020] The present invention uses acrylate emulsion, chloroprene rubber latex and hydrocarbon solvent to jointly construct a modified water-based chloroprene rubber latex system, wherein the acrylate emulsion particles and the chloroprene rubber latex particles are selected from different particle size distribution ranges and are both at the nanometer level. Firstly, the nanometer-level particles have a small particle size and a high surface energy. Therefore, during use, as the solvent gradually evaporates, the acrylate emulsion particles and the chloroprene rubber latex particles are constantly close to each other and can have a strong interaction. In addition, since the particles of the two are selected from different particle size distribution ranges, as the solvent evaporates, an adhesion layer with a higher stacking density can be formed. In this way, a strong cohesive force can be formed during the drying and film-forming process, and the initial adhesion of the product can be effectively improved.
[0021] In the present invention, acrylic emulsion particles and chloroprene latex particles with different particle size distribution ranges are used to construct a modified water-based chloroprene latex system under the action of hydrocarbon solvents. The obtained product can effectively avoid aggregation between particles during storage, and during use, the rapid volatilization characteristics of hydrocarbon solvents are utilized between particles to enable rapid accumulation and aggregation between particles, thereby effectively improving initial bonding performance and drying speed.
[0022] In the present invention, a maleic anhydride surface modifier is used in combination with graphene oxide in a certain ratio, and the maleic anhydride end group reacts with the oxygen-containing group on the surface of the graphene oxide to form esters, and the remaining end group reacts with the double bond of the rubber to modify the performance of the rubber, thereby obtaining greater tensile strength, heat resistance and fatigue resistance. Furthermore, when used in the mortar, the adhesiveness of the coating can be improved, and the effect of bonding can be enhanced. In addition, a preservative is added thereto to extend the bonding time. In the method, a modified maleic anhydride grafted graphene solution is used to prepare styrene-maleic anhydride copolymer grafted graphene oxide at a relatively low reaction temperature. After the product is prepared, its good dispersibility is utilized, and a large number of hydroxyl groups on its surface are used for grafting. Since a large number of anhydride groups are contained in the molecular chain, the reactive active points on the graphene sheet can be effectively increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 This is the modified preparation process of maleic anhydride of the present invention;
[0025] Figure 2 The invention discloses a modified preparation process of the modified graphene chloroprene rubber. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The present invention will be further described below in conjunction with the embodiments.
[0028] Embodiment: A modified graphene chloroprene rubber anticorrosive slurry, the formula ratio by weight is as follows: 100-120 parts of chloroprene rubber slurry, 50-73 parts of dioctyl ester, 2-5 parts of graphene oxide, 20-30 parts of acrylic ester emulsion, 16-20 parts of maleic anhydride grafted graphene solution, 5-10 parts of hydrocarbon solvent, 40-80 parts of water, 3-5 parts of sepiolite, 5-15 parts of preservative.
[0029] The chloroprene rubber slurry includes chloroprene rubber particles, and the particle size distribution range of the chloroprene rubber particles is 60-100nm; the acrylic emulsion includes acrylic ester particles, and the particle size distribution range of the acrylic ester particles is 5-20nm; the modified water-based chloroprene rubber latex system is constructed by using acrylic ester emulsion particles and chloroprene rubber latex particles with different particle size distribution ranges under the action of hydrocarbon solvents, and the obtained product can effectively avoid aggregation between particles during storage, and during use, the rapid volatilization characteristics of hydrocarbon solvents are used between particles to make the particles quickly accumulate and aggregate, and the initial bonding performance and drying speed are effectively improved.
[0030] The hydrocarbon solvent is coated on the surface of the acrylic ester particles and the chloroprene rubber particles, and the hydrocarbon solvent is selected from any one of n-hexane, cyclohexane and isohexane.
[0031] like Figure 1 As shown, the preparation of maleic anhydride grafted graphene solution includes the following steps: S1: preparing graphene oxide by oxidizing natural graphite through Hummers method or improved Hummers method; S2: dispersing the graphene oxide obtained in step S1 and maleic anhydride in an organic solvent (such as dimethylformamide, DMF) to prepare a suspension; S3: grafting maleic anhydride onto the graphene oxide; S4: using the maleic anhydride grafted graphene oxide obtained in step S2 as a raw material, adding a free radical initiator, and reacting with styrene and maleic anhydride at 80-95°C for 1-3 hours; S5: washing the reaction product with a solvent, centrifuging and drying it, to obtain a modified maleic anhydride copolymer grafted graphene.
[0032] The maleic anhydride surface modifier is used in combination with graphene oxide in a certain ratio, and the maleic anhydride end group reacts with the oxygen-containing group on the surface of the graphene oxide to form esters. The remaining end group reacts with the double bond of the rubber to modify the performance of the rubber, thereby obtaining greater tensile strength, heat resistance, and fatigue resistance. When used in the mortar, the adhesiveness of the coating can be improved, the effect of bonding can be enhanced, and a preservative is added thereto to extend the bonding time. In the method, a modified maleic anhydride grafted graphene solution is used to prepare styrene-maleic anhydride copolymer grafted graphene oxide at a relatively low reaction temperature. After the product is prepared, its good dispersibility is utilized, and a large number of hydroxyl groups on its surface are used for grafting. Since the molecular chain contains a large number of anhydride groups, the reactive active points on the graphene sheet can be effectively increased.
[0033] In the process of preparing the maleic anhydride grafted graphene solution, when S2 prepares the suspension, the reaction needs to be maintained at 45-90°C for 2-4 hours, and the mass ratio of graphene oxide to maleic anhydride grafted graphene solution is 2:9-3:30; the sepiolite is a powdered solid, and the free radical initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile or benzoyl peroxide.
[0034] Embodiment 2: A method for preparing an anticorrosive slurry of modified graphene chloroprene rubber, such as Figure 1 As shown, the anti-corrosion slurry including the anti-corrosion slurry in Example 1 is prepared to prepare the anti-corrosion slurry of modified graphene chloroprene rubber, including the following steps: S1: according to the weight parts, 20-30 parts of acrylic emulsion, 100-120 parts of chloroprene rubber slurry, 5-10 parts of hydrocarbon solvent, 40-80 parts of water, and 3-5 parts of sepiolite are taken in sequence; S2: after the sepiolite and water are mixed and dispersed, the acrylic emulsion and chloroprene rubber slurry are added, and after continuing to stir and disperse, the hydrocarbon solvent is added, and the mixture is stirred under pressure and mixed, and then the material is discharged; S3: the graphene oxide is added to 50-60 times of its weight of dioctyl ester, heated to 50-60°C, and stirred at high frequency for 2-8h to obtain product A; S4: maleic anhydride is added; S5: after the sepiolite and water are mixed and dispersed, the product A in S3 is added, and then the hydrocarbon solvent and the preservative are added, and the mixture is stirred under pressure and mixed, and then the material is discharged.
[0035] The graphene oxide is 5-10% of the mass of chloroprene latex; the molar ratio of the graphene oxide to maleic anhydride is 1:1.7-2, the temperature needs to be raised to 70-80°C, and the stirring is continued evenly for 4-6 hours; a modified water-based chloroprene latex system is constructed by using acrylate emulsion, chloroprene latex, and hydrocarbon solvents, wherein the acrylate emulsion particles and the chloroprene latex particles are selected from different particle size distribution ranges, and are all at the nanometer level. Firstly, the nanometer-level particles have a smaller particle size and a higher surface energy. Therefore, during use, as the solvent gradually evaporates, the acrylate emulsion particles and the chloroprene latex particles continue to approach each other and can have a strong interaction. In addition, since the particles of the two are selected from different particle size distribution ranges, as the solvent evaporates, a high stacking density adhesion layer can be formed. In this way, a strong cohesive force can be formed during the drying and film-forming process, effectively improving the initial adhesion of the product.
[0036] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.
Claims
1. A modified graphene chloroprene rubber anticorrosive mortar, characterized in that: The formula proportions are as follows by weight: 100-120 parts of chloroprene rubber paste, 50-73 parts of dioctyl ester, 2-5 parts of graphene oxide, 20-30 parts of acrylic ester emulsion, 16-20 parts of maleic anhydride grafted graphene solution, 5-10 parts of hydrocarbon solvent, 40-80 parts of water, 3-5 parts of sepiolite, and 5-15 parts of preservative.
2. The anti-corrosion mortar of modified graphene chloroprene rubber according to claim 1, characterized in that: The chloroprene rubber slurry includes chloroprene rubber particles, and the particle size distribution range of the chloroprene rubber particles is 60-100 nm. The acrylate emulsion includes acrylate particles, and the particle size distribution range of the acrylate particles is 5-20 nm.
3. The anti-corrosion mortar of modified graphene chloroprene rubber according to claim 1, characterized in that: The hydrocarbon solvent is coated on the surface of the acrylic ester particles and the chloroprene rubber particles, and the hydrocarbon solvent is selected from any one of n-hexane, cyclohexane and isohexane.
4. The anti-corrosion mortar of modified graphene chloroprene rubber according to claim 1, characterized in that: The preparation of maleic anhydride grafted graphene solution comprises the following steps: S1: preparing graphene oxide by oxidizing natural graphite through Hummers method or improved Hummers method; S2: dispersing the graphene oxide obtained in step S1 and maleic anhydride in an organic solvent (such as dimethylformamide, DMF) to prepare a suspension; S3: grafting maleic anhydride onto the graphene oxide; S4: taking the graphene oxide grafted with maleic anhydride obtained in step S2 as a raw material, adding a free radical initiator, and reacting with styrene and maleic anhydride at 80-95° C. for 1-3 hours; S5: washing the reaction product with a solvent, centrifuging and drying it, to obtain a modified maleic anhydride copolymer grafted graphene.
5. The anti-corrosion mortar of modified graphene chloroprene rubber according to claim 4, characterized in that: In the process of preparing the maleic anhydride grafted graphene solution, when S2 prepares the suspension, the reaction needs to be maintained at 45-90°C for 2-4 hours, and the mass ratio of graphene oxide to maleic anhydride grafted graphene solution is 2:9-3:
30.
6. The anti-corrosion mortar of modified graphene chloroprene rubber according to claim 1, characterized in that: The sepiolite is a powdery solid.
7. The anti-corrosion mortar of modified graphene chloroprene rubber according to claim 4, characterized in that: The free radical initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile or benzoyl peroxide.
8. A method for preparing an anti-corrosion mortar of modified graphene chloroprene rubber, characterized in that: The anti-corrosion slurry comprising a modified graphene chloroprene rubber as described in any one of claims 1 to 7, wherein the preparation of the anti-corrosion slurry comprising the modified graphene chloroprene rubber comprises the following steps: S1: Take 20-30 parts of acrylic emulsion, 100-120 parts of chloroprene rubber slurry, 5-10 parts of hydrocarbon solvent, 40-80 parts of water and 3-5 parts of sepiolite in order by weight; S2: After the sepiolite and water are mixed and dispersed, add the acrylic emulsion and chloroprene rubber slurry, continue to stir and disperse, then add the hydrocarbon solvent, pressurize and stir to mix, and then discharge; S3: Add graphene oxide to 50-60 times of its weight of dioctyl ester, heat to 50-60°C, and stir at high frequency for 2-8h to obtain product A; S4: Add maleic anhydride; S5: After the sepiolite and water are mixed and dispersed, add the product A in S3, then add the hydrocarbon solvent and the preservative, pressurize and stir to mix, and then discharge.
9. The anti-corrosion slurry of modified graphene chloroprene rubber and the preparation method thereof according to claim 8, characterized in that: The graphene oxide is 5-10% of the mass of the chloroprene latex.
10. The anti-corrosion mortar of modified graphene chloroprene rubber and the preparation method thereof according to claim 8, characterized in that: The molar ratio of graphene oxide to maleic anhydride is 1:1.7-2, the temperature needs to be raised to 70-80° C., and the mixture is stirred evenly for 4-6 hours.